Low-Dose Aspirin Prevents Kidney Damage in LPS-Induced Preeclampsia by Inhibiting the WNT5A and NF-κB Signaling Pathways - Li, Guanlin; Wei, Wei; Suo, Lingge; Zhang, Chun; Yu, Haiyan; Liu, Hui; Guo, Qing; Zhen, Xiumei; Yu, Yang (Frontiers in Endocrinology, 2021)
Preeclampsia (PE) is a serious pregnancy-related disease, and patients usually present with a high inflammatory response. Previous studies have suggested that aspirin (ASP) may have a role in alleviating the pathogenesis of preeclampsia. However, whether ASP can improve kidney damage and the mechanism for improving it is currently unclear. Here we optimized a lipopolysaccharide (LPS)-induced PE mouse model to identify the role of ASP in renal protection. We found that ASP treatment ameliorated LPS-induced renal failure and pathological changes, the tubular injury was significantly attenuated by ASP. Administration of ASP decreased the renal expression of pro-inflammatory factors, resulting in reduced kidney inflammation. The number of GALECTIN-3-positive cells was reduced, and the up-regulation of IL-6 and TNF-α was decreased. In addition, ASP also suppressed renal cell apoptosis and oxidative stress. An in vitro study indicated that ASP relieved LPS-induced HK-2 cell damage by inhibiting WNT5A/NF-κB signaling. Collectively, our data suggest that ASP is a useful therapeutic option for PE-related kidney injury.